Design and Simulation of a Semi–Automatic Paver Block Making Machine. - Wamani, Samuel (Kabale University, 2024)
Paver block placing by hand takes a lot of time and requires experienced labor. There will be more low-width paved roadways, unsecured loads for carts, and joint fillers (locking sand) due to less competent labor. The creation of an automatic paver block-producing machine with a shorter cycle time was required to solve these issues. The goal of this project is to design and create a low-cost, straightforward machine with an urgent part explanation that will shorten the paver tile block processes' cycle time. Moreover, paver block laying by hand does not call for the soil around the blocks to be made to a particular depth, nor does it necessitate the upkeep and use of machinery for paver block laying. For paver block laying, there are also significant labor, time, and energy expenditures. Road users experience discomfort, noise, and instability on paved roads due to passing cars and trucks. To avoid these issues, interlocking paver blocks may eventually replace bituminous and concrete pavements. These are discovered to be most appropriate for places like sidewalks, narrow streets, and road reconstructions for things like installing phone lines, installing subterranean plumbing, and so forth. The pedestrian streets and squares look more attractive when pavers of various patterns and hues are used. The goal of this project is to develop and build an automatic paver block production machine that can effectively and economically create high-quality paver blocks. To maximize output, cut down on labor needs, and minimize material waste, the machine will make use of sophisticated automation and control technologies. The design will prioritize simplicity of use, upkeep, and repair while guaranteeing uniform block quality and adaptability concerning size, shape, and material type. The machine's design will prioritize safety measures and energy economy, with the goal of producing [X] blocks every hour. The project's product will be a fully operational automatic paver block maker that can satisfy the needs of the construction sector and offer an economical and effective paver block production solution.